Strategy in the contemporary world an introduction to strategic studies - Baylis, John 1946-; Wirtz, James J. 1958-; Gray, Colin S. (Oxford University Press, 2019)
Bringing together international experts to provide a comprehensive introduction to strategic studies, Strategy in the Contemporary World, Sixth Edition, is the only overview to critically engage with both enduring and contemporary issues that dominate strategy. Readers are encouraged to explore key debates and alternative perspectives throughout the chapters. A boxed "Debates" feature considers key controversies and presents opposing arguments, helping students to build critical thinking skills and reflect upon a wide range of perspectives.